PEMBERIAN GELANG IDENTITAS BAYI BARU LAHIR DALAM PERSPEKTIF POSITIVISME HUKUM (PERATURAN MENTERI KESEHATAN NOMOR 1691/MENKES/PER/VIII/2011 TENTANG KESELAMATAN PASIEN RUMAH SAKIT) - Triwahyuniastuti; Eko Ari Wibowo (LPPM institut Teknologi Bisnis AAS Indonesia, 2025)
The research on the provision of newborn baby identity bracelets in hospitals in the perspective of the regulation of the Minister of Health of the Republic of Indonesia number 1691 / MENKES / PER / VII / 2011 aims to determine the views of the provision of baby bracelets from the science of Midwifery documentation and law. The research method is descriptive analytic from midwifery documentation and normative law. Identity bracelets are distinguished by blue for men and red for women. The identity bracelet contains the patient's name By Mrs. Body length. Body weight and address. The results of the study show that the provision of identity bracelets is a form of documentation accountability so that the writing of baby bracelets must be clear. The provision of baby bracelets is very important to provide safety protection to patients by identifying patients, building communication with families and providing continuous treatment. Baby bracelets are very important to prevent the exchange of babies Keywords : Identity bracelet, newborn baby, documentation, obstetrics, law